2021
DOI: 10.1016/j.ssmph.2021.100988
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of suicidal ideation related to the COVID-19 Pandemic: Repeated cross-sectional nationally representative Canadian data

Abstract: Objective With significant levels of mental distress reported by populations, globally, the magnitude of suicidal ideation during and beyond the COVID-19 pandemic is a central concern. The goal of this study was to quantify the extent of pandemic-related suicidal ideation in the Canadian population during the first ten months of the pandemic and identify sociodemographic and pandemic-related stressors associated with increased risk of ideation. Method Data were derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
5
17
0
1
Order By: Relevance
“…First, although we were able to recruit a well-stratified national sample using demographic and regional quotas, possible response biases remain that could limit generalizability to the full Canadian population, particularly given we used exclusively online recruitment and described the study as focusing on mental health. While prevalence estimates should be interpreted cautiously, it is worth noting that our results closely match the distribution of mental health concerns reported in pre-pandemic representative samples ( Government of Canada, 2017 ) and rates of SI reported in nationally representative surveys conducted during the pandemic ( Liu et al, 2021 ; McAuliffe et al, 2021 ). Second, we used a single item to assess current suicidal thoughts.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…First, although we were able to recruit a well-stratified national sample using demographic and regional quotas, possible response biases remain that could limit generalizability to the full Canadian population, particularly given we used exclusively online recruitment and described the study as focusing on mental health. While prevalence estimates should be interpreted cautiously, it is worth noting that our results closely match the distribution of mental health concerns reported in pre-pandemic representative samples ( Government of Canada, 2017 ) and rates of SI reported in nationally representative surveys conducted during the pandemic ( Liu et al, 2021 ; McAuliffe et al, 2021 ). Second, we used a single item to assess current suicidal thoughts.…”
Section: Discussionsupporting
confidence: 77%
“…Second, we used a single item to assess current suicidal thoughts. Although many prior studies have used single items, for instance the ninth item of the PHQ-9 ( Canadian Mental Health Association, 2020 ) or purpose-built items ( Liu et al, 2021 ; McAuliffe et al, 2021 ), to assess SI, this practice may introduce individual biases in respondents' interpretation of the term “suicidal thoughts” as well as the time frame implied by the response option “currently”. While our analysis suggests that the item selected in this study provides a conservative estimate of the prevalence of SI, future studies that include more nuanced questions regarding the nature of these thoughts (e.g., passive versus active ideation, with or without planning) would help further characterize at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…A few longitudinal studies have also analyzed economic stressors at the time of COVID-19 and suicidal thoughts. For example, a Canadian repeated cross-sectional study investigated the prevalence of self-reported suicidal ideation in a nationally representative sample during the COVID-19 pandemic at three time periods between 2020 and 2021 ( 54 ). The results indicated the prevalence of suicidal ideation is increasing over the course of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of COVID-19 related concerns showed that after adjustment for sociodemographic factors, individuals who were experiencing financial stressors, such as concerns about debt and paying bills, had increased risk of suicidal ideation (OR: 2.48, 95% CI: 1.97–3.13). Furthermore, worries about job loss were also associated with increased odds of suicidal ideation (OR: 2.61, 95% CI: 2.07–3.29) ( 54 ). A longitudinal online study from the UK over two timepoints in May and September 2020, examined whether COVID-19 related financial stress and social isolation were associated with suicidal ideation and behavior in a small sample ( n = 370) ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Le stress causé par la pandémie semble avoir touché de façon disproportionnée la santé mentale des jeunes adultes, des personnes racisées et de celles qui vivent avec une maladie mentale 8,11,[16][17][18][19][20] . Les travailleurs de première ligne et les travailleurs essentiels, en particulier les professionnels de la santé, ont aussi dû affronter des risques accrus particuliers en raison de leur exposition à la COVID-…”
Section: Introductionunclassified